Synthesis and preclinical characterization of 1-(6′-deoxy-6′-[18F]fluoro-β-d-allofuranosyl)-2-nitroimidazole (β-6′-[18F]FAZAL) as a positron emission tomography radiotracer to assess tumor hypoxia. Issue 21 (1st November 2016) - Wanek, Thomas; Kreis, Katharina; Križková, Petra; Schweifer, Anna; Denk, Christoph; Stanek, Johann; Mairinger, Severin; Filip, Thomas; Sauberer, Michael; Edelhofer, Patricia; Traxl, Alexander; Muchitsch, Viktoria E.; et al.
Graphical abstract: Abstract: Positron emission tomography (PET) using fluorine-18 ( 18 F)-labeled 2-nitroimidazole radiotracers has proven useful for assessment of tumor oxygenation. However, the passive diffusion-driven cellular uptake of currently available radiotracers results in slow kinetics and low tumor-to-background ratios. With the aim to develop a compound that is actively transported into cells, 1-(6′-deoxy-6′-[ 18 F]fluoro-β-d -allofuranosyl)-2-nitroimidazole (β-[ 18 F]1 ), a putative nucleoside transporter substrate, was synthetized by nucleophilic [ 18 F]fluoride substitution of an acetyl protected labeling precursor with a tosylate leaving group (β-6 ) in a final radiochemical yield of 12 ± 8% ( n = 10, based on [ 18 F]fluoride starting activity) in a total synthesis time of 60 min with a specific activity at end of synthesis of 218 ± 58 GBq/μmol ( n = 10). Both radiolabeling precursor β-6 and unlabeled reference compound β-1 were prepared in multistep syntheses starting from 1, 2:5, 6-di- O -isopropylidene-α-d -allofuranose. In vitro experiments demonstrated an interaction of β-1 with SLC29A1 and SLC28A1/2/3 nucleoside transporter as well as hypoxia specific retention of β-[ 18 F]1 in tumor cell lines. In biodistribution studies in healthy mice β-[ 18 F]1 showed homogenous tissue distribution and excellent metabolic stability, which was unaffected by tissue oxygenation. PET studies in tumor bearing mice showed tumor-to-muscle ratios of 2.13 ± 0.22 ( n = 4) at 2 h after administration of β-[ 18 F]1 . In ex vivo autoradiography experiments β-[ 18 F]1 distribution closely matched staining with the hypoxia marker pimonidazole. In conclusion, β-[ 18 F]1 shows potential as PET hypoxia radiotracer which merits further investigation.